HIV is hyperendemic among men who have sex with men in San Francisco: 10-year trends in HIV incidence, HIV prevalence, sexually transmitted infections and sexual risk behaviour. Issue 6 (21st November 2008) - Scheer, S; Kellogg, T; Klausner, J D; Schwarcz, S; Colfax, G; Bernstein, K; Louie, B; Dilley, J W; Hecht, J; Truong, H-H M; Katz, M H; McFarland, W
Abstract : Objectives: To evaluate trends in the HIV epidemic among men who have sex with men (MSM) in San Francisco and the implications for HIV prevention. Methods: An ecological approach assessed temporal trends in sexual risk behaviour, sexually transmitted infections (STI), HIV incidence and prevalence from multiple data sources between 1998 and 2007. Results: By 2007, there were over 13 000 HIV-infected MSM living in San Francisco. No consistent upward or downward temporal trends were found in HIV incidence, newly reported HIV cases, AIDS deaths, proportion of AIDS cases using antiretroviral therapy, rectal gonorrhoea or primary and secondary syphilis cases among MSM during the study period. Trends in indicators of sexual risk behaviour among MSM were mixed. Overall, unprotected anal intercourse (UAI) increased in community-based surveys. Among HIV-positive MSM, no significant trends were noted for UAI. Among HIV-negative MSM, UAI with unknown serostatus partners decreased but increased with potentially discordant serostatus partners. Among MSM seeking HIV testing, increases were noted in insertive UAI at anonymous testing sites and at the STI clinic, in receptive UAI at anonymous test sites and in receptive UAI with a known HIV-positive partner at the STI clinic. Conclusions: Temporal trends in multiple biological and behavioural indicators over the past decade describe a hyperendemic state of HIV infection among MSM in San Francisco, whereby prevalence has stabilised at a very high level. In the absence of new, effective prevention strategies this state will persist.